PERBANDINGAN DESAIN PENGERING BERBASIS EFEK RUMAH KACA VARIASI CEROBONG PENGHAWAAN: IMPLEMENTASI PADA MASYARAKAT LOKAL - Djamalu, Yunita (Program Vokasi-Universitas Negeri Gorontalo, 2024)
Greenhouse effect-based dryers are an efficient and environmentally friendly technological solution to improve the quality and added value of agricultural and fishery products. This research aims to analyze the comparative technical and economic performance of three variations of ventilation chimney designs, namely conventional, thermal, and multidirectional, in their implementation in local communities. Research methods include field experiments to measure technical parameters, such as temperature, humidity, drying time, and airflow speed, and economic analysis to calculate investment costs, payback period, and net profits. The results showed that the thermal chimney provided the best performance with an average temperature of 50°C, drying time of 21 hours, and high airflow efficiency, suitable for rural areas. Multidirectional chimneys are more flexible against unstable wind conditions, making them ideal for coastal areas. This technology is environmentally friendly with a reduction in carbon emissions of up to 1.2 tonnes of CO₂ per year per unit. The novelty of this research lies in the combination of innovative design, in-depth economic analysis, and the application of technology that is adaptive to local needs and challenges, making it relevant and beneficial to society and the environment. In conclusion, a greenhouse effect-based dryer with a ventilation chimney design is a technology that is feasible to apply to increase productivity, environmental sustainability, and the welfare of local communities.